Reproducibility of hybrid capture ii second generation for high grade HPV detection in cervico-vaginal selfcollecting samples - Cremonesi, Adriana; Taromaru, Eliane; Dôres, Gerson Botacini das; Castelo, Adauto; Longatto Filho, Adhemar; Veras, Tânia Maria CW; Holanda Júnior, Francisco (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: the cervical cancer, although the prevention is possible, is the third cause of death in women population in Brazil. According to NationalInstitute of Cancer (INCA) occurs annually about 17.000 new cases in Brazil, with mortality rate estimated in 4.000 cases. Human papillomavirus (HPV)is the main factor of risk associated with this type of cancer. Some types of HPV, called high risk, are oncogenics and are found in practically 100% ofthe cervical tumors and in the majority of the high-grade lesions. Thus, the clinical application of molecular tests for detection of the HPV in the cervico-vaginal samples, as strategy of selection of cervical cancer and high-grade lesions, generated great interest. Objective:the present work had for objectiveto compare the results of Hybrid Capture II for HPV high risk in specimens collected by doctor and by self-collection. Methods:hybrid capture detectionof oncogenic HPV (STM, DIGENE Corp., USA) from medical and self-collecting samples were compared. The study was approved by the HealthAuthorities of Ceará State, which indicated the four cities to participate: Crato, Juazeiro do Norte, Sobral and Pedra Branca. Were included women fromone of these cities for this study with age ranging from 15 to 50 years old, and the last Papanicolaou test performed a least more than 6 months. Results:of 323 evaluated women, 17.96% were positive for both collection methods, 73.37% had presented resulted negative for both the collection methods,1.86% were positive by medical collection and negative by self-collection and, 6.81% were positive by self-collection and negative by medical collec-tion. Conclusion:we can conclude that self-collection, for HPV detection is so efficient on routine screening for oncogenic HPV types as the collectionperformed by professionals of the health.Keywords: HPV, self-sampling, hybrid captureISSN: 0103-0465DST – J bras Doenças Sex Transm 16(4):5-10, 2004ARTIGOARTICLE1.Bióloga formada pela Universidade de Santo Amaro (UNISA), pós graduanda emQualidade e Produtividade Empresarial: Logística e Gestão de Processos pelo IPT(USP) e Encarregada de Produção da Digene Brasil. 2.Gerente Técnica da Digene Brasil, São Paulo, Brasil.3.Diretor Científico da Digene Brasil, São Paulo, Brasil.4.Professor Adjunto de Doenças Infecciosas da Escola de Medicina da UniversidadeFederal de São Paulo, São Paulo, Brasil5.Pesquisador Científico do Instituto Adolfo Lutz, São Paulo, Brasil, Postdoctoral fel-lowship Universidade do Minho, Escola de Ciências da Saúde, Braga, Portugal.6.Diretora do Instituto de Prevenção do Câncer do Ceará (IPCC), médica, ginecologistae obstetra , coordenadora do Programa de Prevenção do Câncer de Colo do Útero doEstado do Ceará e mestranda em ginecologia pela UFCE.7.Médico, ginecologista e obstetra da Secretaria de Saúde do Estado do Ceará.